2013
DOI: 10.1103/physrevlett.110.177208
|View full text |Cite
|
Sign up to set email alerts
|

Surpassing Fundamental Limits of Oscillators Using Nonlinear Resonators

Abstract: In its most basic form an oscillator consists of a resonator driven on resonance, through feedback, to create a periodic signal sustained by a static energy source. The generation of a stable frequency, the basic function of oscillators, is typically achieved by increasing the amplitude of motion of the resonator while remaining within its linear, harmonic regime. Contrary to this conventional paradigm, in this Letter we show that by operating the oscillator at special points in the resonator’s anharmonic regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
96
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(103 citation statements)
references
References 32 publications
6
96
1
Order By: Relevance
“…Some time ago, Greywall et al demonstrated an interesting noise quenching effect in the operation of a self-oscillating system [1,2], a discovery that has an important potential impact for the design of high frequency, low noise electronic oscillators [3,4]. In addition to its practical consequences, the noise quenching phenomenon is of fundamental interest because it appeared when the system operated in the nonlinear regime, i.e., the quenching apparently relies on the inherent nonlinearity of the resonating element.…”
Section: Introductionmentioning
confidence: 99%
“…Some time ago, Greywall et al demonstrated an interesting noise quenching effect in the operation of a self-oscillating system [1,2], a discovery that has an important potential impact for the design of high frequency, low noise electronic oscillators [3,4]. In addition to its practical consequences, the noise quenching phenomenon is of fundamental interest because it appeared when the system operated in the nonlinear regime, i.e., the quenching apparently relies on the inherent nonlinearity of the resonating element.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear effects strongly restrict the dynamic range within which the system operates linearly, even making it vanishingly small in NEMS, and limit the scope for applications. However, recent works focus on directly using nonlinearities to improve the sensitivity of parametrically amplified detectors [16,18,19]. For instance, though quartic (Duffing) nonlinearities stabilize the parametric oscillator, it retains a "memory" of the underlying instability tongue structure in its frequency dependent response [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the most limiting difficulties for the practical development of batch-fabricated SiNW resonators with performance characteristics approaching those of CNTs is to establish highly sensitive transduction schemes that efficiently convert mechanical vibrations into functional electrical signals. The small amplitude of the mechanical vibrations, in combination with their very high frequency and the natural tendency of high-aspect ratio beams to operate in a nonlinear regime, represents formidable obstacles for such purpose 11,12 . The application of the most sensitive transduction schemes reported so far for nanomechanical resonators, such as piezoelectric 13 , electrothermal 14 or optomechanical 15 , results either impossible or impractical for simple beams made of silicon with dimensions deep down in the nanoscale and resonant frequencies in the very high-frequency range.…”
mentioning
confidence: 99%